STATINS AND MYOPATHY: MOLECULAR MECHANISMS - O. M. Drapkina; E. M. Chernova; O. N. Korneeva (Столичная издательская компания, 2015)
The safety of statin therapy is considered. In particular the reasons of a complication such as myopathy are discussed in detail. The molecular mechanisms of statin myopathy , as well as its risk factors are presented. The role of coenzyme Q10 in the myopathy development and coenzyme Q10 application for the prevention of this complication are considered.